Eksplorasi Keberlanjutan Kajian Peran Taman Toga Dalam Pemberdayaan Masyarakat Desa Kesamben - Angela, Martha; Umniyya Aisyah; Yayuk Widyastuti Herawati (Makkareso: Riset Pengabdian Masyarakat, 2024)
In the cultivation of family medicinal plants (Toga), women's farming groups in Kesamben Village face several challenges that need to be addressed. Some of the main obstacles include limited access to technological information, lack of financial support from the village government—forcing members to self-fund the cultivation—and land constraints. As the group expands and the number of cultivated plants increases, these challenges become more complex. This study aims to analyze the challenges faced in the cultivation of Toga plants by women's farming groups and formulate strategies to ensure the sustainability of the program. The research employs a descriptive qualitative method, utilizing both primary and secondary data sources. Primary data is collected through interviews and direct observations, while secondary data comes from various references such as books, articles, and scientific journals. The findings indicate that the medicinal plants cultivated in the community’s Toga garden in Kesamben Village include leek, aromatic ginger (Kaempferia galanga), ginger (Zingiber officinale), greater galangal (Alpinia galanga), and mother of thousands (Kalanchoe pinnata). Additionally, peanuts are also planted temporarily to make use of vacant land before the main seedlings arrive. The presence of Toga plants plays a crucial role in community empowerment, particularly by providing alternative natural medicines that can be used in daily life. To ensure the sustainability of Toga cultivation, collaboration among various stakeholders is necessary to optimize plant diversity and support the village’s health resilience